ANALISIS PENGARUH PENANAMAN MODAL ASING, PENDAPATAN ASLI DAERAH DAN KETIMPANGAN PENDAPATAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN MIMIKA - Shandy Eka Prastya; Selmi Tandi Lembang, Josael Maatoke (Adisam Publisher, 2025)
This study aims to determine the influence of foreign investment, regional original income, and income inequality in the human development index in Mimika Regency, both partially and simulaneously. The method used is this study is associative. The data collection technique employed by the researchers is documentation. The analytical tool used in this research is multipe linear regression analysis. The results of the study indicate that foreign investment, regional original income, and income inequality partially do not significantly affect the human development index in Mimika Regency, However, simultaneously, foreign investment, regional original income, and income inequality significantly affect the human development index in Mimika Regency